Examining the relationship between subjective sleep disturbance and menopause: a systematic review and meta-analysis - Xu, Qunyan; Lang, Cathryne P (Menopause (New York, N.Y.), 2014)
The purpose of this study was to conduct a systematic review and meta-analysis of the relationship between menopausal stages and sleep disturbance reported using subjective methods. Secondary aims included examining the influence of culture/ethnicity on the relationship between menopausal stages and sleep disturbance. Multiple electronic databases were searched from the first available year to November 2013, and a manual search of the reference lists of review articles identified was also conducted. Twenty-four studies with a total of 63,542 midlife women were identified, coded, and analyzed. The crude and adjusted odds of experiencing sleep disturbance were small but statistically significant for perimenopausal and postmenopausal women, using premenopause as the reference group. The ethnicity of the samples influenced effect sizes; Asian and white women both experienced an increased rate of sleep disturbance at the perimenopausal and postmenopausal stages compared with the premenopausal stage, whereas Hispanic women experienced no change in sleep disturbance across the menopausal transition. The prevalence of sleep disturbance is higher in perimenopausal, postmenopausal, and surgical menopausal women than in premenopausal women. There is an independent relationship between menopausal stages and sleep disturbance beyond the effects of aging and other confounders, although the magnitude of the relationship is small. Culture, ethnicity, or both might affect the levels of sleep disturbance at various menopausal stages.